Role of probiotics in urogenital healthcare - Santosh S Waigankar; Vimal Patel (Wolters Kluwer Medknow Publications, 2011)
Urogenital infections are one of the most common causes for a woman to visit a gynecologist or a urologist. The well-known association between abnormal vaginal microbial flora and its formidable risk in the increased incidence of urinary tract infection underscores the importance of understanding the microbial flora and the efforts needed to maintain it, for ensuring urogenital health. Surprisingly in spite of the increased incidence urogenital infections receive very less attention from the medical fraternity. Growing awareness among people and newer advances in the medical field has brought them into the limelight. The importance of replenishing these depleting commensals with 'probiotics' has resurfaced in a big way. As the days go by science and medicines will touch new milestones, which will include probiotics. The value of a probiotics cannot be taken at face value. Probiotics must not be considered a panacea for treating urogenital infections. However, the available data promises that it will be a strong option in improving and maintaining urogenital health.